2017
DOI: 10.1002/ijc.30727
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal lung cancer screening using the ITALUNG biomarker panel and low dose computed tomography. Results of the ITALUNG biomarker study

Abstract: Asymptomatic high-risk subjects, randomized in the intervention arm of the ITALUNG trial (1,406 screened for lung cancer), were enrolled for the ITALUNG biomarker study (n = 1,356), in which samples of blood and sputum were analyzed for plasma DNA quantification (cut off 5 ng/ml), loss of heterozygosity and microsatellite instability. The ITALUNG biomarker panel (IBP) was considered positive if at least one of the two biomarkers included in the panel was positive. Subjects with and without lung cancer diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 27 publications
0
31
0
1
Order By: Relevance
“…In addition to these models comprised of classical phenotypes, some researchers discovered biomarkers to improve the prediction accuracy of the models [33]. The ITALUNG biomarker panel (IBP) combined with low-dose computed tomography achieved good performance for the identification of lung cancers at baseline screening, with a sensitivity of 90.0% and specificity of 89.0% [34]. A study suggested that a panel of four biomarkers composed of prolactin, CRP, NY-ESO-1, and HGF to screen for lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these models comprised of classical phenotypes, some researchers discovered biomarkers to improve the prediction accuracy of the models [33]. The ITALUNG biomarker panel (IBP) combined with low-dose computed tomography achieved good performance for the identification of lung cancers at baseline screening, with a sensitivity of 90.0% and specificity of 89.0% [34]. A study suggested that a panel of four biomarkers composed of prolactin, CRP, NY-ESO-1, and HGF to screen for lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed earlier, integrating molecular studies into LDCT screening programs provides a unique opportunity to resolve some of these problems. This modality has already been adopted in some recent large programs [ 22 24 ]. For example, a biomarker panel composed of plasma DNA and genomic analyses in the ITALUNG biomarker study was as sensitive as LDCT (90%) and increased screening specificity from 71% (LDCT alone) to 89% via a multimodal approach [ 22 ].…”
Section: Study Area 2: Precise Screening With Insights From Molecularmentioning
confidence: 99%
“…This modality has already been adopted in some recent large programs [ 22 24 ]. For example, a biomarker panel composed of plasma DNA and genomic analyses in the ITALUNG biomarker study was as sensitive as LDCT (90%) and increased screening specificity from 71% (LDCT alone) to 89% via a multimodal approach [ 22 ]. Another diagnostic test consisting of seven autoantibodies is currently under a randomized controlled trial among 12,000 Scotsmen, aiming to examine whether pre-screening with this test would be helpful to identify high-risk candidates, thereby increasing the overall effectiveness of LDCT screening [ 23 ].…”
Section: Study Area 2: Precise Screening With Insights From Molecularmentioning
confidence: 99%
“…Es fand sich eine hohe Übereinstimmung eines positiven Biomarker-Befunds mit der Karzinomdiagnose. Der positive Vorhersagewert (PPV) stieg von 4,3 % für die LDCT-Diagnostik allein auf 10,6 % bei der Kombination von LDCT und Biomarker-Panel [23]. Dies sind erste Hinweise, dass zukünftig eine Kombination von blutbasierter Diagnostik mit einem LDCT-Screening eine gezieltere Selektion von Risikopersonen ermöglichen könnte.…”
Section: Ct-screening Für Das Lungenkarzinom: Evidenz Für Den Nutzenunclassified